2015
DOI: 10.1111/febs.13267
|View full text |Cite
|
Sign up to set email alerts
|

PKC‐mediated inhibitory feedback of the cholecystokinin 1 receptor controls the shape of oscillatory Ca2+ signals

Abstract: Translation of extracellular hormonal input into cellular responses is often mediated by repetitive increases in cytosolic free Ca 2+ concentration ([Ca 2+ ] c ). Amplitude, duration and frequency of these so-called [Ca 2+ ] c oscillations then carry information about the nature and concentration of the extracellular signalling molecule. At present, there are different hypotheses concerning the induction and control of these oscillations. Here, we investigated the role of agonist-induced receptor phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…An increase of cytosolic Ca 2+ could stimulate phosphatidylserine scrambling and induce eryptosis . The concentration of cytosolic Ca 2+ is regulated by many factors such as Gardos K( + ) channels (Foller et al, 2010), platelet activating factor (PAF) (Xu et al, 2009), prostaglandin (Muravyov and Tikhomirova, 2014), and protein kinase C Willems et al, 2015). Our results showed that the decreased intracellular Ca 2+ prevented phosphatidylserine scrambling in hypoxia.…”
Section: Discussionmentioning
confidence: 71%
“…An increase of cytosolic Ca 2+ could stimulate phosphatidylserine scrambling and induce eryptosis . The concentration of cytosolic Ca 2+ is regulated by many factors such as Gardos K( + ) channels (Foller et al, 2010), platelet activating factor (PAF) (Xu et al, 2009), prostaglandin (Muravyov and Tikhomirova, 2014), and protein kinase C Willems et al, 2015). Our results showed that the decreased intracellular Ca 2+ prevented phosphatidylserine scrambling in hypoxia.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies of CCK signal transduction in vagal afferents indicate that PKA, PLA 2 , and PI 3 K are not required for CCK-induced calcium responses and that the prominent point of control is likely via PLC cleavage of PIP 2 and subsequent gating of transient receptor potential (TRP) channels and/or L-type voltage-activated calcium channels (15,48,49). Nonetheless, both CCK receptors and ion channel effectors are strongly regulated by site specific phosphorylation via PKC and PKA subtypes, suggesting these parallel pathways may shape the magnitude and time-dependent changes in CCK signaling (43,46).…”
Section: Introductionmentioning
confidence: 99%
“…In dissociated vagal afferent neurons, CCK concentration dependently evokes depolarizing currents and elevates cytosolic calcium from extracellular sources (14,25). While the magnitudes of these responses are a result of CCK receptor density and the number of associated ion channel effectors, the signal desensitization is a function of CCK concentration and subsequent receptor occupancy (43). The CCK1R has both high-and low-affinity binding sites (13,31,41) that are coupled to different signaling cascades in pancreatic acinar cells (9,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Regarding increased intracellular calcium ion concentration ([Ca 2+ ]i) in acutely ill bipolar patients and the suggested antimanic effect of calcium channel blockers, it is notable that activation of PKC inhibits the influx of calcium across the membrane, which is suggestive of the relation between modulated calcium signaling and antimanic effects of PKC inhibitors. 4,5 Currently, tamoxifen is the only relatively specific PKC inhibitor capable of crossing blood-brain barrier that has been available for human use. 6 In recent years, several controlled trials evaluated the efficacy of tamoxifen in the treatment of acute manic episodes, as either monotherapy or adjunct.…”
mentioning
confidence: 99%